Factors Affecting Tourist Satisfaction and Revisit Intention in Pokhara - Sapkota, Pradeep (Journal of Development and Social Engineering, 2024)
This study investigated the factors affecting tourist satisfaction and revisit intention in Pokhara, Nepal. The sample consisted of 616 respondents from Pokhara, and data was collected through a self-administered questionnaire. The researchers used frequency percentage analysis, means score analysis, and structural equation modeling for data analysis using IBM SPSS AMOS. The findings revealed that infrastructure, price, IT and safety and security had a significant impact on both tourist satisfaction whereas only infrastructure had significant impact on revisit intention. This study suggests that understanding and these factors can enhance the tourist experience, encourage repeat visits, and promote sustainable tourism development in Pokhara, Nepal.